Purification of the antichagasic benznidazole from the commercial preparation Rochegan®: characterization of inclusion complexes with β-cyclodextrin - Espinosa Silva, Yanis Ricardo (2018)
The Chagas is a endemic disease from the American continent whose etiological agent is the Trypanosoma cruzi. Currently, there is neither a prophylactic vaccine for this disease or a totally effective treatment for the chronic cases. The Nifurtimox and the benznidazole are nitroheterocyclic complexes that have been used since the end of the 60’s and the beginning of the 70’s, mainly for the treatment of congenital and acute infections. However, these medications can cause a wide variety of adverse effects. Especially, in the benznidazole is necessary to develop new therapeutic alternatives which improve its low solubility in water, the limited gastrointestinal absorption, and the high toxicity. Because of the difficulties that often occur in the achievement of pre-synthesis Benznidazole, high costs in the synthesis process and buy the active compound in countries with limited research economics commodities. We have proposed a method of purification in order to facilitate the experimental procedures from the commercial preparation Rochegan®, obtaining BNZ viable for the formation of the controlled release complex with β-cyclodextrin (βCD) and the characterization of the BNZ-βCD inclusion complex.